Connection structure, manufacturing method thereof, connection material, and coated conductive particles
Patent Information
- Application Number
- JP2024166460
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-05-01
- Filing Date
- 2024-09-25
- Publication Date
- 2025-04-03
AI Technical Summary
Conventional conductive particles exhibit high and unstable conduction resistance values, failing to meet the demands of diverse connection needs and reliability tests.
A connection structure using coated conductive particles with a core particle, a conductive layer, and metal fine particles, where metal atoms from the conductive layer diffuse into the metal fine particles during thermocompression bonding, forming a stable conductive bond.
The solution significantly reduces and stabilizes the conduction resistance value, ensuring reliable electrical connections by enhancing conductivity and resistance to variations over time.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present technology relates to a connection structure in which electronic components are connected, a method for manufacturing a connection structure, a connection material, and coated conductive particles. [Background technology]
[0002] Conventionally, connecting materials containing conductive particles have been used for electrical connection of circuits, etc. Known conductive particles include those having uneven surfaces (see, for example, Patent Document 1), those coated with metal filler (see, for example, Patent Document 2), and those coated with insulating filler (see, for example, Patent Document 3).
[0003] However, in recent years, the objects to be connected using conductive particles have become more diverse, and in addition to improving insulation performance, there is a demand for lowering and stabilizing the conductive resistance value. For this reason, with conventional conductive particles, the conductive resistance value is high compared to such demands, and there are also cases where the conductive resistance value varies widely after reliability tests. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2005-317270 A [Patent Document 2] JP 2013-041683 A [Patent Document 3] JP 2018-145418 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present technology has been proposed in consideration of the above-described conventional situation, and provides a connection structure, a manufacturing method for a connection structure, a connection material, and coated conductive particles that can reduce and stabilize the conductive resistance value. [Means for solving the problem]
[0006] The connection structure according to the present technology comprises a first electronic component having a first terminal, a second electronic component having a second terminal, and a cured film between the first terminal and the second terminal, which is formed by hardening a connection material containing coated conductive particles having core material particles, a conductive layer provided on the surface of the core material particles, and metal fine particles coating the surface of the conductive layer, and the coated conductive particles between the first terminal and the second terminal are formed by metal atoms of the conductive layer diffusing into the metal of the metal fine particles, and metal atoms of the first terminal and metal atoms of the second terminal diffusing into the metal of the metal fine particles.
[0007] A method for manufacturing a connection structure according to the present technology includes thermocompression bonding a first electronic component having a first terminal and a second electronic component having a second terminal at a predetermined temperature via a connecting material containing coated conductive particles having a core particle, a conductive layer provided on the surface of the core particle, and metal fine particles coating the surface of the conductive layer, and for the coated conductive particles between the first terminal and the second terminal, metal atoms of the conductive layer are diffused into the metal of the metal fine particles, and metal atoms of the first terminal and the second terminal are diffused into the metal of the metal fine particles.
[0008] The connecting material according to the present technology comprises coated conductive particles, each of which comprises a core particle, a conductive layer provided on the surface of the core particle, and metal fine particles coating the surface of the conductive layer, dispersed in an insulating binder, and the metal atoms of the conductive layer diffuse into the metal of the metal fine particles at a predetermined temperature during thermocompression bonding.
[0009] The coated conductive particles according to the present technology comprise a core particle, a conductive layer provided on the surface of the core particle, and metal microparticles coating the surface of the conductive layer, and the metal atoms of the conductive layer diffuse into the metal of the metal microparticles at a predetermined temperature during thermocompression bonding. Effect of the Invention
[0010] According to this technology, by thermocompression bonding, the metal atoms of the conductive layer of the coated conductive particles between the terminals diffuse into the metal of the metal microparticles, and the metal atoms of the terminals also diffuse into the metal of the metal microparticles, thereby reducing and stabilizing the conductive resistance value. [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic diagram of a connection structure. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a schematic diagram of a connection structure on which a camera module is mounted. [Diagram 3] FIG. 3 is an SEM photograph of the resin-core conductive particles (Ni (undercoat) / Au (surface) plating (Au=35 μm, Ni=210 nm), resin core, with protrusions) used in Example 2. [Figure 4] FIG. 4 is an SEM photograph of the coated conductive particles (fine metal particles: silver particles of 60 μm) used in Example 2. [Diagram 5] FIG. 5 is an SEM photograph of a cross section of the connection part of the connection structure produced in Example 2. As shown in FIG. [Figure 6] FIG. 6 is an enlarged photograph of the ceramic substrate side of the square portion shown in FIG. [Figure 7] FIG. 7 is a silver (Ag) mapping image of the enlarged photograph portion shown in FIG. [Figure 8] FIG. 8 is a mapping image of nickel (Ni) in the enlarged photograph portion shown in FIG. [Figure 9] FIG. 9 is a gold (Au) mapping image of the enlarged portion of the photograph shown in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, embodiments of the present invention will be described in detail with reference to the drawings in the following order. 1.Coated conductive particles 2. Connection materials 3. Manufacturing method of connecting material 4. Connection structure 5. Manufacturing method of connection structure 6. Working Example
[0013] <1. Coated conductive particles> The coated conductive particles in this embodiment comprise a core particle, a conductive layer provided on the surface of the core particle, and metal microparticles coating the surface of the conductive layer, and the metal atoms of the conductive layer diffuse into the metal of the metal microparticles at a predetermined temperature during thermocompression bonding.
[0014] Here, in this specification, "diffusion" refers to the diffusion of metal atoms of the conductive layer or metal atoms of the terminal of the electronic component into the metal of the metal fine particles, or the diffusion of metal atoms of the metal fine particles into the metal of the conductive layer or the metal of the terminal of the electronic component due to heat, pressure, deformation, etc. Such a diffusion state can be observed by line analysis or element mapping of the contact portion between the coated conductive particle and the terminal of the electronic component using an energy dispersive X-ray analyzer (EDS) with a transmission electron microscope FE-TEM.
[0015] Examples of the core particles include resin particles, organic-inorganic hybrid particles, and metal particles. Examples of the resin constituting the resin particles include styrene-divinylbenzene copolymer, benzoguanamine resin, crosslinked polystyrene resin, acrylic resin, and styrene-silica composite resin. Examples of the organic-inorganic hybrid particles include particles formed of crosslinked alkoxysilyl polymer and acrylic resin. Examples of the metal particles include nickel, cobalt, silver, copper, gold, palladium, and solder. Among these, it is preferable to use resin particles and organic-inorganic hybrid particles that have excellent stress relaxation properties.
[0016] The conductive layer is provided on the surface of the core particle. The metal of the conductive layer is preferably one whose metal atoms diffuse into the metal of the metal fine particles at a predetermined temperature during thermocompression bonding, and any metal that does not diffuse but has conductivity upon contact with the metal fine particles can be used. The predetermined temperature during thermocompression bonding is, for example, 200°C or less, preferably 160°C or less, and more preferably 140°C or less. The metal of the conductive layer can be appropriately selected according to the metal of the metal fine particles. The conductive layer is preferably at least one simple metal or alloy of nickel, silver, copper, gold, and palladium. The conductive layer may also be solder. When the core particle is a metal particle, the conductive layer is preferably at least one simple metal or alloy of gold and palladium to prevent surface oxidation. In addition, from the viewpoint of conductivity and surface oxidation, the conductive layer preferably has a first conductive layer and a second conductive layer in this order on the surface of the core particle, and it is preferable that the first conductive layer is a nickel plating layer and the second conductive layer is a gold plating layer.
[0017] The thickness of the conductive layer is preferably 50 nm or more and 300 nm or less, more preferably 80 nm or more and 250 nm or less. When the conductive layer is composed of a plurality of metal layers, it is preferable that the total thickness satisfies the above range. If the thickness of the conductive layer is too small, it becomes difficult to make it function as a conductive particle. In addition, when the core material particle is a metal particle, its surface can be regarded as the conductive layer, and the thickness of the conductive layer does not need to be particularly considered. Hereinafter, regardless of the type of core material particle, one composed of a core material particle and a conductive layer is referred to as a "conductive particle". In addition, one in which the core material particle is a resin particle may be referred to as a "resin core conductive particle".
[0018] The conductive particles preferably have a plurality of protrusions on the surface of the conductive layer. The configuration of the conductive particles having protrusions is not particularly limited as long as the surface of the conductive layer has a shape having protrusions, and for example, the following first to third configuration examples can be mentioned. The first configuration example includes a core particle, insulating particles attached to the surface of the core particle in multiple numbers to become the core material of the protrusions, and a conductive layer covering the core particle and the insulating particles. The second configuration example includes a core particle, insulating particles attached to the surface of the core particle in multiple numbers to become the core material of the protrusions, a first conductive layer covering the surfaces of the core particle and the insulating particles, and a second conductive layer covering the first conductive layer. The third configuration example includes a core particle, a first conductive layer covering the surface of the core, insulating particles attached to the surface of the first conductive layer in multiple numbers to become the core material of the protrusions, and a second conductive layer covering the surfaces of the first conductive layer and the insulating particles. By having multiple protrusions on the surface of the conductive layer, the amount of metal particles attached can be increased with the protrusions as cores, and the conductive resistance value can be further reduced and stabilized. In addition, by the protrusions digging into the surface of the terminal to be connected, the effect of diffusion of the metal particles covering the conductive layer and the metal atoms on the terminal surface can be made more pronounced. This can be inferred for various reasons, such as the pressure on the metal particles covering the conductive layer being increased by the protrusions, or simply the contact area being increased.
[0019] The lower limit of the particle diameter of the conductive particles is preferably 2 μm or more. The upper limit of the particle diameter of the conductive particles is not particularly limited, but from the viewpoint of the capture efficiency of the conductive particles in the connection structure, for example, it is preferably 50 μm or less, and more preferably 20 μm or less. The particle diameter of the conductive particles can be a value measured by an image type particle size distribution meter (for example, FPIA-3000: manufactured by Malvern Instruments). The number is preferably 1000 or more, preferably 2000 or more.
[0020] The metal fine particles cover the surface of the conductive layer provided on the surface of the core particle. The metal of the metal fine particles can be appropriately selected according to the metal of the conductive layer and the metal of the terminal of the electronic component. The metal fine particles are preferably at least one elemental metal or alloy of nickel, silver, copper, gold, and palladium. The metal fine particles may also be solder. Among these, silver or a silver alloy is preferable from the viewpoint of reducing resistance.
[0021] The upper limit of the particle diameter of the metal fine particles can be 14% or less, preferably 0.3% or less, of the conductive particles. Alternatively, it is preferably 100 nm or less, and more preferably 80 nm or less. This allows the metal of the conductive layer and the metal of the terminal of the electronic component to be diffused into the metal of the metal fine particles by thermocompression bonding. In addition, since the particle diameter of the metal fine particles is not too large compared to the surface area of the conductive particles, defects such as scratches on the surface of the conductive particles can be suppressed. In addition, the lower limit of the particle diameter of the metal fine particles may be 2 nm or more, and is preferably 10 nm or more. Since the metal fine particles are not too small compared to the surface area of the conductive particles, the aggregation of the conductive particles can be more effectively suppressed. If the metal fine particles are too small, the viscosity of the connecting material increases too much, which may affect the dispersibility. The particle diameter of the metal fine particles can be, for example, observed with an electron microscope (e.g., TEM) and can be the average value of any 100 particles, and the accuracy can be improved by making it 200 particles or more.
[0022] As described above, the coated conductive particles can preferably use solder particles as metal fine particles. The solder particles preferably cover the surfaces of the resin core conductive particles. By using the resin core conductive particles, the resin core of the resin core conductive particles deforms and repels during connection, making it easier to obtain a uniform connection state. In addition, resin core conductive particles generally have less variation in particle size than metal particles. Specifically, the coefficient of variation (CV value) of the resin core conductive particles is 20% or less, preferably 10% or less, and more preferably 5% or less. The small variation in particle size makes it easier to make the pressure applied to the resin core uniform during connection. In this way, the deformation and repulsion of the resin core and the uniformity of the particle size of the resin core conductive particles make it easier to stably hold the conductive particles between the terminals, so the connection state (joining state) between the terminals is more stable than when metal particles are used, and stabilization of the conductive resistance can be expected. This is because the contact state between the terminal and the electrode is stabilized, and by guaranteeing the state (amount and area) of the solder joint to the electrode, it is expected that connection failures will be less likely to occur.
[0023] The solder particles can be appropriately selected from, for example, Sn-Pb, Pb-Sn-Sb, Sn-Sb, Sn-Pb-Bi, Bi-Sn, Sn-Cu, Sn-Pb-Cu, Sn-In, Sn-Ag, Sn-Pb-Ag, Pb-Ag, etc., as specified in JIS Z 3282-1999, according to the electrode material, connection conditions, etc. The lower limit of the melting point of the solder particles is preferably 110°C or higher, more preferably 120°C or higher, and even more preferably 130°C or higher. The upper limit of the melting point of the solder particles is preferably 240°C or lower, more preferably 200°C or lower, and even more preferably 150°C or lower. By heating the solder particles to a predetermined temperature, the metal atoms of the solder particles and the metal atoms of the conductive layer can be easily mutually diffused, and the metal atoms of the solder particles and the metal atoms of the terminals can be easily mutually diffused. The solder particles may contain the same metal as that contained in the resin-core conductive particles, such as Ni. By containing the same metal as that contained in the resin-core conductive particles in the solder particles, it is expected that the affinity between the solder particles and the metal layer of the resin-core conductive particles is increased. The particle size of the solder particles is in the same range as that of the above-mentioned metal microparticles.
[0024] The coated conductive particles may be those in which the surface of the resin particle, which is the core particle, is coated with solder particles. The coated conductive particles may be those in which the surface of the resin particle, which is the core particle, is coated with metal fine particles other than solder particles. By coating the surface of the resin particle with solder particles, the solder particles can be melted by heating to form a conductive layer of solder on the surface of the resin particle. The coated conductive particles may be those further coated with metal fine particles that can easily mutually diffuse the metal atoms of the solder particles and the metal atoms of the terminal as described above.
[0025] The coated conductive particles may be resin core conductive particles or resin particles whose surfaces are coated with a mixture of solder particles and a flux compound. Examples of the flux compound include carboxylic acids such as levulinic acid, maleic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, and sebacic acid. By using the flux compound, a good bonding state can be obtained.
[0026] Also, as described above, the coated conductive particles may be conductive particles having protrusions as shown in the first to third configuration examples, the surfaces of which are coated with metal fine particles, or insulating particles that become protrusions may be mixed with metal fine particles to coat them. The Mohs hardness of the insulating particles is preferably greater than 7. Examples of insulating particles include zirconia (Mohs hardness 8 to 9), alumina (Mohs hardness 9), tungsten carbide (Mohs hardness 9), and diamond (Mohs hardness 10), which may be used alone or in combination of two or more. Among these, it is preferable to use alumina from the viewpoint of economic efficiency. If there is an oxide on the electrode surface, the protrusions can break through the oxide due to the high hardness of the insulating particles, and a good bonding state can be obtained.
[0027] Coating of metal fine particles can be performed by applying the method described in JP 2018-145418 A, for example. The method is not limited to the method described in the examples described later, and is not particularly limited as long as the same effect can be obtained. In addition to coating by a dry method, a liquid component or a viscous liquid component may be mixed and coated by the same operation.
[0028] <2. Connection materials> The connecting material according to the present embodiment is formed by dispersing the coated conductive particles described above in an insulating binder. Examples of the connecting material include a conductive adhesive that exhibits conductivity for connecting a first electronic component and a second electronic component, and an anisotropic conductive adhesive that exhibits conductivity only in the direction of pressure application. The connecting material can also be used as a via material (filler) that connects between layers of a wiring board, a wiring material for a wiring pattern, and the like.
[0029] Hereinafter, an anisotropic conductive adhesive will be described as an example. The anisotropic conductive adhesive may be either a film-shaped anisotropic conductive film (ACF: Anisotropic Conductive Film) or a paste-shaped anisotropic conductive paste (ACP: Anisotropic Conductive Paste). In terms of ease of handling, an anisotropic conductive film is preferred, and in terms of cost, anisotropic conductive paste is preferred. The lower limit of the thickness of the anisotropic conductive film may be, for example, the same as the particle diameter, and may be preferably 1.3 times or more the particle diameter or 10 μm or more. The upper limit of the thickness of the anisotropic conductive film may be, for example, 40 μm or less or 2 times or less the particle diameter. The anisotropic conductive film may be formed on a release film. The anisotropic conductive film may be laminated with an adhesive layer or a pressure-sensitive adhesive layer that does not contain conductive particles, and the number of layers and the lamination surface can be appropriately selected according to the target or purpose. The insulating resin of the adhesive layer or the pressure-sensitive adhesive layer may be the same as that of the anisotropic conductive film.
[0030] The insulating binder (insulating resin) may be a known insulating binder. Examples of the curing type include a heat curing type, a photocuring type, and a photothermal combined curing type. Examples of the curing type include a photoradical polymerization type resin composition containing a (meth)acrylate compound and a photoradical polymerization initiator, a thermal radical polymerization type resin composition containing a (meth)acrylate compound and a thermal radical polymerization initiator, a thermal cationic polymerization type resin composition containing an epoxy compound and a thermal cationic polymerization initiator, and a thermal anionic polymerization type resin composition containing an epoxy compound and a thermal anionic polymerization initiator. A known adhesive composition may also be used. Note that the present technology is not limited to the insulating binder (insulating resin) described above. Also, the (meth)acrylate compound in the following embodiment is merely an example for explaining the invention.
[0031] In this embodiment, a thermosetting insulating binder that cures at a predetermined temperature during thermocompression bonding is suitable. In the following, as a specific example, a thermal radical polymerization insulating binder containing a film-forming resin, an elastomer, a (meth)acrylic monomer, a polymerization initiator, and a silane coupling agent will be described. Note that the (meth)acrylic monomer includes both an acrylic monomer and a methacrylic monomer.
[0032] The film-forming resin is not particularly limited, and examples thereof include phenoxy resin, unsaturated polyester resin, saturated polyester resin, urethane resin, butadiene resin, polyimide resin, polyamide resin, and polyolefin resin. The film-forming resin may be used alone or in combination of two or more. Among these, it is particularly preferable to use phenoxy resin from the viewpoints of film-forming property, processability, and connection reliability. The phenoxy resin is a resin synthesized from bisphenol A and epichlorohydrin, and may be appropriately synthesized or may be a commercially available product. The content of the film-forming resin is not particularly limited, and is preferably, for example, 10% by mass to 60% by mass.
[0033] The elastomer is not particularly limited, and examples thereof include polyurethane resin (polyurethane-based elastomer), acrylic rubber, silicone rubber, and butadiene rubber.
[0034] The (meth)acrylic monomer is not particularly limited, and may be, for example, a monofunctional (meth)acrylic monomer or a polyfunctional (meth)acrylic monomer having two or more functional groups. From the viewpoint of stress relaxation of the polymer, it is preferable that 80 mass % or more of the (meth)acrylic monomers in the insulating binder are monofunctional (meth)acrylic monomers.
[0035] From the viewpoint of adhesion, the monofunctional (meth)acrylic monomer preferably has a carboxylic acid. The molecular weight of the monofunctional (meth)acrylic monomer having a carboxylic acid is preferably 100 to 500, and more preferably 200 to 350. The content of the monofunctional (meth)acrylic monomer having a carboxylic acid in the insulating binder is preferably 3% by mass to 20% by mass, and more preferably 5% by mass to 10% by mass.
[0036] The polymerization initiator is not particularly limited as long as it can harden the (meth)acrylic monomer at a predetermined temperature during thermocompression bonding, and examples thereof include organic peroxides. Examples of organic peroxides include lauroyl peroxide, butyl peroxide, benzyl peroxide, dilauroyl peroxide, dibutyl peroxide, peroxydicarbonate, and benzoyl peroxide. These may be used alone or in combination of two or more. The content of the polymerization initiator in the insulating binder is not particularly limited, and is preferably, for example, 0.5% by mass to 15% by mass. The predetermined temperature during thermocompression bonding can be determined from the reaction initiation temperature of the polymerization initiator and the polymerizable compound that reacts therewith. This is because the predetermined temperature during thermocompression bonding is generally set higher than the reaction initiation temperature. The predetermined temperature during thermocompression bonding also depends on the connection time and reactivity (latency, life), and therefore also depends on the connection conditions.
[0037] The silane coupling agent is not particularly limited, and examples thereof include epoxy-based silane coupling agents, acrylic-based silane coupling agents, thiol-based silane coupling agents, amine-based silane coupling agents, etc. The content of the silane coupling agent in the insulating binder is not particularly limited, and is preferably, for example, 0.1% by mass to 5.0% by mass.
[0038] <3. Method for manufacturing connecting material> The method for producing the connecting material according to the present embodiment includes the following steps (A) and (B).
[0039] [Process (A)] In step (A), the conductive particles and metal fine particles are stirred to obtain coated conductive particles in which the conductive particles are coated with metal fine particles. In addition, by using conductive particles having a plurality of protrusions on the surface of the conductive layer, the protrusions become nuclei for the attachment of the metal fine particles, and the amount of the attached metal fine particles can be increased.
[0040] The particle diameters of the conductive particles and metal fine particles are in the same range as those described for the coated conductive particles. The conductive particles and metal fine particles can be commercially available products. In addition, it is preferable to use the conductive particles in a dry powder state from the viewpoint of coating with the metal fine particles.
[0041] In step (A), the conductive particles and the metal fine particles are preferably mixed so that the amount of the metal fine particles relative to the conductive particles is, for example, less than 200% by volume. The amount of the metal fine particles relative to the conductive particles (volume %) can be determined by the following formula.
[0042] The amount (volume %) of metal particles (B) relative to the conductive particles (A) ={(Bw / Bd) / (Aw / Ad)}×100 Aw: Mass composition of conductive particles (A) (mass%) Bw: Mass composition of metal particles (B) (mass%) Ad: Specific gravity of conductive particles (A) Bd: Specific gravity of metal particles (B)
[0043] By satisfying these conditions, the coating of the metal fine particles on the surfaces of the conductive particles can be easily progressed in step (A). As described above, even when a liquid or viscous liquid component such as a flux compound is stirred simultaneously with the metal fine particles, it is sufficient to satisfy the above conditions.
[0044] The method of stirring the conductive particles and the metal fine particles may be either a dry method or a wet method, and the dry method is preferred. This is because the method used in known toners and the like can be applied. Examples of devices for stirring the conductive particles and the metal fine particles include planetary stirring devices, shakers, lab mixers, stirring propellers, and the like. In particular, from the viewpoint of coating the conductive particles with metal fine particles having a small particle size, a planetary stirring device with a high shear is preferred. The planetary stirring device can obtain a mixture containing the coated conductive particles and the metal fine particles by rotating and revolving a container containing the conductive particles and the metal fine particles.
[0045] [Process (B)] In the step (B), the mixture containing the coated conductive particles and the metal fine particles is stirred with the insulating binder to obtain a connecting material in which the coated conductive particles are dispersed in the insulating binder.
[0046] In addition, in process (B), friction or high shear between the metal fine particles in the coated conductive particles and the conductive particles may cause the metal fine particles to detach from the conductive particles. However, since the detached metal fine particles are interposed between the coated conductive particles, aggregation of the coated conductive particles is suppressed.
[0047] In this way, by carrying out step (B), it is possible to suppress the aggregation of the coated conductive particles and disperse the coated conductive particles in the insulating binder. In addition, in step (B), since the insulating binder is added to the mixture containing the coated conductive particles and the metal fine particles obtained in step (A), the same container and the same device can be used, and material costs and manufacturing costs can be reduced.
[0048] The method for producing a connecting material according to the present embodiment may further include other steps in addition to the above-mentioned steps (A) and (B) as necessary. For example, when the connecting material is a film-shaped anisotropic conductive film, the step may include forming a film of an anisotropic conductive adhesive composition in which coated conductive particles are dispersed in an insulating binder by a coating method, and drying the film.
[0049] <4. Connection structure> FIG. 1 is a cross-sectional view showing a connection part of the connection structure according to the present embodiment. The connection structure according to the present embodiment includes a first electronic component 1 having a first terminal 1a, a second electronic component 2 having a second terminal 2a, and a cured film formed by curing the above-mentioned connection material between the first electronic component 1 and the second electronic component 2. The coated conductive particles 3 between the first terminal 1a and the second terminal 2a are formed by diffusing metal atoms of the conductive layer into the metal of the metal fine particles, and by diffusing metal atoms of the metal of the first terminal and the metal of the second terminal into the metal of the metal fine particles. As a result, the metal of the first terminal and the metal of the second terminal are in a state of being metallically bonded and alloyed with the metal of the metal fine particles, so that the conduction resistance value can be reduced and stabilized. In the above, an anisotropic conductive connection in which the wiring of the electronic component has lines and spaces (L / S) has been described, but the terminals (wiring) of the electronic component may be a so-called solid pattern, and may be used as a conductive connection or a conductive adhesive without anisotropy (not shown). The terminals do not necessarily have to be convex, but may be any current-carrying portions that are electrically connected.
[0050] The first electronic component and the second electronic component are not particularly limited and can be appropriately selected depending on the purpose. Examples of the first electronic component include flexible printed circuits (FPC), glass substrates, and plastic substrates. Examples of the second electronic component include camera modules, integrated circuit (IC) modules, and IC chips. The second electronic component may be a functional module equipped with a sensor. In camera modules, ceramic substrates are sometimes used because of their excellent electrical insulation and thermal insulation properties. Ceramic substrates and functional modules are used in order to reduce the size (for example, to less than 1 cm). 2The connection structure to which this technology is applied has the advantage of being excellent in dimensional stability in semiconductor devices (see below). In addition, the connection structure to which this technology is applied can be used in any electronic device that uses electrical connections, such as semiconductor devices (including driver ICs as well as all devices that use semiconductors, such as optical elements, thermoelectric conversion elements, and photoelectric conversion elements), display devices (monitors, televisions, head-mounted displays, etc.), mobile devices (tablet devices, smartphones, wearable devices, etc.), game consoles, audio devices, imaging devices (using image sensors such as camera modules), electrical mounting for vehicles (mobile devices), medical devices, and sensor devices (touch sensors, fingerprint authentication, iris authentication, etc.).
[0051] In the following, a connection structure having a camera module mounted thereon will be described as a specific example. Fig. 2 is a cross-sectional view showing a connection structure having a camera module mounted thereon. As shown in Fig. 2, this connection structure includes a flexible substrate 10 having a first terminal, a camera module 20 having a second terminal, and a cured film 30 formed by curing the above-mentioned connection material between the first terminal and the second terminal.
[0052] A first terminal is provided at a position facing a second terminal of the camera module on the flexible substrate 10. Furthermore, a camera module driving IC 11 may be mounted on the flexible substrate 10 in addition to the camera module mounting portion.
[0053] 2, camera module 20 has a ceramic substrate 21 having a recess (cavity) on its mounting surface and a second terminal on the periphery of the recess, an image sensor 22 housed in the recess, a protective glass 23 arranged on image sensor 22 and fixed on ceramic substrate 21, and a lens 24 arranged on image sensor 22 and installed in a housing. As shown in FIG. 2, ceramic substrate 21 has second terminals formed on two or three opposing sides of its rectangular mounting surface.
[0054] The cured film 30 is the aforementioned connecting material cured, and is obtained, for example, as shown in FIG. 3, by attaching an anisotropic conductive film 31 onto the rectangular mounting surface of a ceramic substrate 21, and then thermocompressing the flexible substrate 10 mounted on the anisotropic conductive film 31.
[0055] A connection structure having such a configuration can shorten the distance T1 between the image sensor 22 and the flexible substrate 30. It is optically difficult to shorten the distance between the image sensor 22 and the lens 24.
[0056] In addition, since the camera module 20 has a recess on the mounting surface, gas tends to accumulate in the recess after mounting, and when a reliability evaluation test is performed at high pressure, for example, the flexible substrate 10 may swell due to the influence of the gas. According to this embodiment, the metal atoms of the conductive layer of the coated conductive particles are diffused into the metal of the metal fine particles, and the metal atoms of the first terminal and the metal atoms of the second terminal are diffused into the metal of the metal fine particles. This allows metal bonding and alloying to proceed, and the camera module 20 and the flexible substrate 10 are firmly bonded, so that low resistance can be stably maintained. Therefore, signals can be stably transmitted and received to and from the image sensor 22, and a captured image (electrical signal) with reduced noise can be obtained.
[0057] In the present technology, the metal of the conductive portion to be connected, the metal of the conductive layer of the conductive particles, and the metal of the metal fine particles coating the conductive particles can be appropriately selected according to their combination. For example, the metal of the first terminal, the metal of the second terminal, and the metal of the conductive layer of the conductive particles are preferably the same type. This allows the same type of metal bonding and alloying to proceed, and migration between different metals can be prevented. In addition, as an example of the configuration of the terminals, it is preferable that the first terminal and the second terminal are formed in this order by forming a nickel plating layer and a gold plating layer on a conductor. This allows the conductive layer of the coated conductive particles to be formed from a first conductive layer that is nickel or a nickel alloy and a second conductive layer that is gold or a gold alloy, and when the metal fine particles are silver or a silver alloy, gold atoms are diffused into the silver or silver alloy by thermocompression bonding, forming an intermetallic compound of gold and silver, thereby preventing migration of silver and nickel. The diffusion of metal atoms in this technology is thought to be due to the influence of the metal's free electrons, and it is presumed that the high mobility of the metal's free electrons in metal microparticles contributes to the alloying of the metal microparticles (silver as mentioned above) with the target metal (gold as mentioned above).
[0058] <5. Method for manufacturing connection structure> In the method for manufacturing the connection structure according to the present embodiment, a first electronic component having a first terminal and a second electronic component having a second terminal are thermocompression-bonded at a predetermined temperature via the above-mentioned connection material, and the metal atoms of the conductive layer are diffused into the metal of the metal fine particles, and the metal atoms of the first terminal and the second terminal are diffused into the metal of the metal fine particles. This makes it possible to reduce and stabilize the resistance of the conductive resistance value. Here, the predetermined temperature during thermocompression bonding is, for example, 200°C or less, preferably 160°C or less, and more preferably 140°C or less. The temperature of 200°C or less is an index set from the viewpoint of suppressing the effect of suppressing thermal shock to the target member during connection (such as reducing warping of the substrate) and suppressing distortion after hardening, which will be described later. When a temperature of 200°C or more is required to diffuse the metal atoms of the first terminal, the metal atoms of the second terminal, and the metal atoms of the conductive layer of the conductive particles into the metal of the metal fine particles, the target member during connection, the material and thickness of the connection material, etc. may be used according to the heat resistance. The predetermined temperature during thermocompression bonding is equal to or higher than the hardening start temperature of the connecting material, so that the predetermined temperature during thermocompression bonding can be determined by measuring the hardening start temperature.
[0059] The thermocompression bonding temperature may be 200° C. or less at which metal diffusion occurs, and is preferably 160° C. or less, and more preferably 140° C. or less. A lower thermocompression bonding temperature is preferable because it reduces the thermal shock applied to the first electronic component and the second electronic component.
[0060] The first electronic component and the second electronic component are the same as the first electronic component and the second electronic component in the connection structure described above, and the connection material is also the same as the connection material described above. EXAMPLES
[0061] Hereinafter, an example of the present technology will be described. In this example, coated conductive particles using silver particles as metal fine particles were prepared. Then, a connection structure was prepared using an anisotropic conductive film containing the coated conductive particles, and the conductive characteristics were evaluated. In addition, a cross section of the connection part of the connection structure was observed. <Example 1>
[0062] [Preparation of conductive particles] Three parts by mass of resin-core conductive particles (Ni (base) / Au (surface) plating, resin core, no protrusions) with an average particle size of 20 μm and one part by mass of silver particles with an average particle size of 60 nm as metal particles were added to a planetary mixing device (product name: Awatori Rentaro, manufactured by THINKY Corporation) and stirred for five minutes to produce a mixture containing coated conductive particles.
[0063] [Preparation of anisotropic conductive film] Five parts by mass of the mixture containing the coated conductive particles and 95 parts by mass of an insulating binder consisting of the following components were added to a planetary mixer (product name: Awatori Rentaro, manufactured by THINKY Corporation) and stirred for one minute to produce an anisotropic conductive adhesive composition. The anisotropic conductive adhesive composition was then applied to a PET film and dried in an oven at 80°C for five minutes to form an adhesive layer consisting of the anisotropic conductive adhesive composition on the PET film, producing an anisotropic conductive film having a width of 2.0 mm and a thickness of 25 μm.
[0064] The insulating binder was a mixed solution of ethyl acetate and toluene containing 47 parts by mass of phenoxy resin (product name: YP-50, manufactured by Shinnikka Epoxy Manufacturing Co., Ltd.), 3 parts by mass of monofunctional monomer (product name: M-5300, manufactured by Toagosei Co., Ltd.), 25 parts by mass of urethane resin (product name: UR-1400, manufactured by Toyobo Co., Ltd.), 15 parts by mass of rubber component (product name: SG80H, manufactured by Nagase ChemteX Corporation), 2 parts by mass of silane coupling agent (product name: A-187, manufactured by Momentive Performance Materials Japan), and 3 parts by mass of organic peroxide (product name: Niper BW, manufactured by NOF Corporation) so that the solid content was 50% by mass.
[0065] [Fabrication of connection structure] A camera module evaluation substrate (ceramic substrate, 200μm pitch, line:space=1:1, terminal thickness 10μm, Ni(base) / Au(surface) plating, with cavity structure) and FPC (polyimide film, 200μm pitch, line:space=1:1, terminal thickness 12μm, Ni(base) / Au(surface) plating) were thermocompression bonded via anisotropic conductive film to create a connection structure. Thermocompression bonding was performed by pressing a tool down via a 200μm thick silicone rubber on the FPC under the conditions of temperature: 120℃, pressure: 1MPa, and time: 6sec.
[0066] <Example 2> An anisotropic conductive film and a connection structure were produced in the same manner as in Example 1, except that 3 parts by mass of resin core conductive particles (Ni (base) / Au (surface) plating, resin core, with protrusions) with an average particle size of 20 μm and 0.5 parts by mass of silver particles with an average particle size of 60 nm as metal particles were added to a planetary stirrer to produce a mixture containing coated conductive particles.
[0067] <Example 3> An anisotropic conductive film and a connection structure were produced in the same manner as in Example 1, except that 3 parts by mass of resin core conductive particles (Ni (base) / Au (surface) plating, resin core, with protrusions) with an average particle size of 20 μm and 1 part by mass of silver particles with an average particle size of 60 nm as metal particles were added to a planetary stirrer to produce a mixture containing coated conductive particles.
[0068] <Comparative Example 1> An anisotropic conductive film and connection structure were prepared in the same manner as in Example 1, except that 5 parts by mass of resin core conductive particles (Ni (base) / Au (surface) plating, resin core, with protrusions) with an average particle size of 20 μm and 95 parts by mass of insulating binder were added to a planetary stirring device to prepare an anisotropic conductive adhesive composition.
[0069] <Evaluation of Conduction Characteristics> Using a digital multimeter (manufactured by Yokogawa Electric Corporation), the conductive resistance value of the connection structure was measured when a current of 1 mA was applied using the four-terminal method. In addition, the conductive resistance value of the connection structure was measured after a reliability evaluation test (12h, 24h) under conditions of a temperature of 121°C, humidity of 100%, and atmospheric pressure of 2 atm. The conductive resistance value of the connection structure was measured on 6 channels per sample, for a total of 20 samples (120 channels).
[0070] Table 1 shows the conduction resistance values (maximum, average, minimum) of the connection structure initially and after the reliability evaluation test (12 h, 24 h).
[0071] [Table 1]
[0072] As shown in Table 1, in Comparative Example 1, which used protruding conductive particles not coated with silver particles, the difference between the maximum and minimum values of the conductive resistance was large, and the difference between the maximum and minimum values of the conductive resistance became even larger after the reliability evaluation test. Furthermore, in Comparative Example 1, the average value of the conductive resistance increased after the reliability evaluation test.
[0073] On the other hand, in Example 1, which used coated conductive particles in which protruding non-conductive particles were coated with silver fine particles, and in Examples 2 and 3, which used coated conductive particles in which protruding conductive particles were coated with silver fine particles, the difference between the maximum and minimum values of the conduction resistance was small, and the difference between the maximum and minimum values of the conduction resistance became even smaller after the reliability evaluation test. In addition, in Examples 1 to 3, the average value of the conduction resistance decreased after the reliability evaluation test. This is considered to be because the diffusion of the metal became more widespread after the reliability evaluation test. It was also found that good results were obtained by mixing and stirring 0.5 to 1.0 parts by mass of silver particles with 3 parts by mass of conductive particles.
[0074] <Cross-section observation of connection part> FIG. 3 is a scanning electron microscope (SEM) photograph of the resin core conductive particles (Ni (base) / Au (surface) plating (Au=35 μm, Ni=210 nm), resin core, with protrusions) used in Example 2, and FIG. 4 is a SEM photograph of the coated conductive particles (metal fine particles: silver particles 60 μm) used in Example 2. From FIGS. 3 and 4, it can be seen that by mixing and stirring the conductive particles with protrusions and the silver particles, the silver particles adhere to each other so as to cover the protrusions.
[0075] In addition, the metal diffusion state was observed by using a transmission electron microscope (FE-TEM) and an energy dispersive X-ray analyzer (EDS) to perform elemental mapping of the contact area between the coated metal particles in the connection structure of Example 2 and the terminals on the ceramic substrate side (Ni (base) / Au (surface) plating).
[0076] Fig. 5 is an SEM photograph of a cross section of the connection part of the connection structure produced in Example 2, and Fig. 6 is an enlarged photograph of the ceramic substrate side of the square part shown in Fig. 5. Fig. 7 is a mapping image of silver (Ag) of the enlarged photograph part shown in Fig. 6. Fig. 8 is a mapping image of nickel (Ni) of the enlarged photograph part shown in Fig. 6. Fig. 9 is a mapping image of gold (Au) of the enlarged photograph part shown in Fig. 6.
[0077] From FIG. 7, it can be seen that silver, which is a metal fine particle, exists at the contact portion between the coated metal particle and the terminal on the ceramic substrate side. Also, from FIG. 8, it can be seen that a metal other than nickel exists between the nickel of the conductive layer of the coated metal particle and the nickel of the terminal on the ceramic substrate side. Also, from FIG. 9, it can be seen that gold has diffused into the silver existing between the nickel of the conductive layer of the coated metal particle and the nickel of the terminal on the ceramic substrate side. That is, from FIG. 7 to FIG. 9, it can be seen that the Au atoms of the Au plating of the terminal of the ceramic substrate and the Au atoms of the Au plating of the conductive layer of the coated conductive particle have diffused into the Ag of the metal fine particles. This is presumed to be because the particle size of the metal fine particles is small, so that the number of metal fine particles in contact with the Au of the top surface of the conductive layer and the Au of the top surface of the terminal increases, making it easier for Au to diffuse into the Ag of the metal fine particles, and it is presumed that the relatively large mobility of the free electrons of the metal of the metal fine particles affects the alloying of the conductive layer and the plating layer of the terminal as described above.
[0078] In the above embodiment, the diffusion of metal fine particles is described, but it is not limited thereto, and may be, for example, simple contact with metal fine particles or alloying. Depending on the material, the metal fine particles may achieve the purpose if they can obtain a conductive performance between the conductive layer of the resin core conductive particle or the conductive particle. This is because the coated conductive particles are coated with metal fine particles, and factors that contribute to conduction, such as an increase in the contact points and contact area of the metal fine particles with the conductive particles, are also overlapped. The effect of the diffusion of the metal fine particles described above may be replaced by these factors. [Explanation of symbols]
[0079] 1 first electronic component, 1a first terminal, 2 second electronic component, 2a second terminal, 3 coated conductive particles, 10 flexible substrate, 11 camera module driving IC, 20 camera module, 21 ceramic substrate, 22 image sensor, 23 protective glass, 24 lens, 30 cured film, 31 anisotropic conductive film
Claims
1. Core particles; A conductive layer provided on a surface of the core particle; and metal fine particles attached to a surface of the conductive layer, Coated conductive particles in which metal atoms of the conductive layer diffuse into the metal of the metal fine particles at a predetermined temperature during thermocompression bonding.
2. A method for producing coated conductive particles, comprising stirring conductive particles having a core particle and a conductive layer provided on the surface of the core particle with metal fine particles, and adhering the metal fine particles to the surface of the conductive layer.
3. a first electronic component having a first terminal; a second electronic component having a second terminal; a cured film formed by curing a connection material containing coated conductive particles having core particles, a conductive layer provided on a surface of the core particles, and metal fine particles attached to a surface of the conductive layer, between the first electronic component and the second electronic component; The coated conductive particles between the first terminal and the second terminal are formed by the metal atoms of the conductive layer diffusing into the metal of the metal microparticles, and the metal atoms of the first terminal and the metal atoms of the second terminal diffusing into the metal of the metal microparticles, forming a connection structure.
4. An insulating binder; The present invention includes a coated conductive particle including a core particle, a conductive layer provided on a surface of the core particle, and metal fine particles attached to the surface of the conductive layer, A connecting material in which metal atoms of the conductive layer diffuse into the metal of the metal fine particles at a predetermined temperature during thermocompression bonding.
5. An insulating binder; The present invention includes a coated conductive particle including a core particle, a conductive layer provided on a surface of the core particle, and metal fine particles attached to the surface of the conductive layer, An anisotropic conductive film in which metal atoms of the conductive layer diffuse into the metal of the metal fine particles at a predetermined temperature during thermocompression bonding.
6. 6. The anisotropic conductive film according to claim 5, wherein the core particles are made of resin particles.
7. A first electronic component; A second electronic component; A cured film obtained by curing the connection material according to claim 4 or the anisotropic conductive film according to claim 5 or 6 is provided between the first electronic component and the second electronic component. A connection structure comprising:
8. A method for manufacturing a connection structure, in which a first electronic component and a second electronic component are thermocompression bonded at a predetermined temperature via the connecting material described in claim 4 or the anisotropic conductive film described in claim 5 or 6.
9. Conductive particles including core particles and a conductive layer provided on the surface of the core particles and metal fine particles are stirred to prepare coated conductive particles in which the metal fine particles are attached to the surface of the conductive layer; A method for producing a connecting material, comprising stirring a mixture containing the coated conductive particles and the metal fine particles with an insulating binder.
10. A method for producing coated conductive particles having a core particle and a conductive layer provided on a surface of the core particle, the conductive particles being mixed with metal fine particles, and the metal fine particles being attached to a surface of the conductive layer; A method for producing an anisotropic conductive film, comprising mixing a mixture containing the coated conductive particles and the metal fine particles with an insulating binder, and forming the mixture into a film.
11. A method for producing a conductive material comprising: a conductive layer formed on the surface of the core particle; and coated conductive particles having metal fine particles adhered to the surface of the conductive layer, the method comprising: thermocompressing a first electronic component having a first terminal and a second electronic component having a second terminal at a predetermined temperature via a connecting material in which metal atoms of the conductive layer diffuse into the metal of the metal fine particles at a predetermined temperature during thermocompression bonding; A method for manufacturing a connection structure, in which, for coated conductive particles between the first terminal and the second terminal, metal atoms of the conductive layer are diffused into the metal of the metal fine particles, and metal atoms of the first terminal and metal atoms of the second terminal are diffused into the metal of the metal fine particles.